Police officers' awareness of the speech, language and communication needs of young offenders. (December 2021) - MacRae, AnneMarie; Clark, Ann
Around 60% of young people in conflict with the law experience speech, language and communication needs (SLCN). This study investigates Police Scotland officers' awareness of the SLCN of young offenders, strategies officers use to support SLCN and their interest in further training on SLCN. A majority had worked with young offenders with SLCN and were fairly confident in recognising these needs. The most common support strategy was to involve outside agencies, specifically Appropriate Adults. Increased speech and language therapy services are needed to train Police Officers to recognise and support SLCN without reliance on other agencies.